Cervical Pessaries for the Prevention of Preterm Birth: A Systematic Review - Sophie M. S. Liem; Mariëlle G. van Pampus; Ben Willem J. Mol; Dick J. Bekedam (Obstetrics and Gynecology International)
Introduction. Reduction of preterm birth is a major goal in obstetric care. We performed a systematic review of randomized controlled trials and cohort studies on the effectiveness of the cervical pessary to prevent preterm birth. Methods. We searched the electronic databases of MEDLINE and Embase from inception until April 2012 to identify studies investigating treatment with a cervical pessary to prevent preterm birth. We constructed two-by-two tables for delivery before 28, 34, and 37 weeks of gestation and calculated relative risks (RRs) with 95% confidence intervals. Results. The search revealed 103 potentially eligible abstracts of which six cohort studies and four randomized controlled trials (RCTs) investigated the effectiveness of the pessary. One RCT (n=380) demonstrated a lower delivery rate prior to 34 weeks (RR 0.24; 95% CI 0.13–0.43) in the pessary group, while another RCT (n=108) showed no positive effect of pessary for delivery before 34 weeks (RR 1.73; 95% CI 0.43–6.88). Two older quasi randomized studies and cohort studies indicated potential effect of the pessary. Conclusions. Available randomized and nonrandomized studies indicate potential effectiveness of a cervical pessary in the prevention of preterm birth. More randomized clinical trials are needed before this device can be used in clinical practice.